Strategic Management in Public Library: Empowering Community Reading Habits at Regional Level - Fitra Fitra; Rusdin Rusdin; Masmur Masmur; Irawan Hadi Patanggu; Andi Nurfaizah (at-Tahsin, 2026)
This study aims to explore the strategic management approaches executed to enhance public reading habits within the geographically fragmented context of regional public libraries. The problem addresses the declining trend of sustained community reading interest and library underutilization, which is further exacerbated by severe geographical isolation, administrative inertia, and resource constraints in developing regional districts. To address this issue, this study employs a qualitative case study design focused on the Regional Public Library of Tojo Una-Una Regency, Central Sulawesi. Data were meticulously gathered through triangulated instruments, including semi-structured interviews with key administrative and community informants, field observations of outreach initiatives, and comprehensive institutional document reviews. The qualitative data were then analyzed using an interactive model comprising systematic data condensation, structural data display, and continuous conclusion verification to ensure interpretive trustworthiness. The empirical findings reveal that the chief librarian successfully neutralized severe geographical fragmentation by shifting from centralized operations to a decentralized, network-based distribution model. Management optimized limited resources by building cross-sector alliances and deploying an innovative, amphibious book-box rotation system using local maritime transportation networks to regularly reach marginalized island communities. Based on these insights, future research should employ mixed-methods approaches across diverse regional typologies to evaluate how digital literacy platforms can be integrated into this collaborative strategic management framework.